The salt mines of Maras: Organization and conflict - Palomino Meneses, Abdón (1985)
In the month of November 1981. The city of Cusco was invaded by hundreds of peasants from the neighboring district of Maras on a sacrificial march, claiming the benefits of their salt mines for the whole town, demanding the departure of the trading company (EMSAL). ) and requesting the municipalization of their resource. Fleetingly, the name of Maras appeared in the information media of Cusco and the capital of the Republic. The terms of his claim did not attract much attention, although the State was forced to accept them. In the opinion of many, the Government of that time erred in weakness by handing over to a district municipality the commercialization of the salt to be withdrawn from the state company, the "only one empowered by law to commercialize salt, a basic and first-priority industry" (D.L. 17387-PCM-69).